Dietary Copper-Zinc Ratio and Type 2 Diabetes Risk in Women: The E3N Cohort Study. (29th May 2020) - Laouali, Nasser; MacDonald, Conor-James; Fatouhi, Douae El; Mancini, Francesca Romana; Fagherazzi, Guy; Boutron-Ruault, Marie-Christine
Abstract: Objectives: Trace elements are essential minerals that are required for a variety of biological processes. Zinc (Zn) is a trace element involved in many biological processes including regulation of insulin and glycaemia. It has been suggested that the serum copper (Cu) to Zn ratio could be of importance towards risk of diabetes. However, little is known about the effect of suboptimal intakes of these two competitive trace elements. We aimed to investigate the association between type 2 diabetes (T2D) incidence and the dietary Cu-Zn, ratio. Methods: A total of 70, 991 women from the E3N ( Etude Epidémiologique auprès de femmes de la Mutuelle Générale de l'Education Nationale ) cohort study were followed for 20 years. The individual daily energy-adjusted intakes of Cu and Zn were estimated at baseline using a validated food frequency questionnaire. T2D cases were identified and validated using diabetes-specific questionnaires and drug reimbursement insurance databases. Multivariable Cox regression models estimated hazard ratios (HRs) and 95% confidence intervals (CIs) between dietary Cu-Zn ratio intakes and T2D risk. Interactions were tested between Cu-Zn ratio and smoking status and BMI on incident T2D. Results: A total of 3292 incident T2D cases were identified during follow-up. A lower Cu-Zn ratio was associated with a lower risk of T2D. Compared to the 1st quintile group, women from the 2nd (HR 0.87 [95% CI 0.78, 0.97]) and 3rd (HR 0.89 [95% CI 0.79, 0.99]) quintile groups had a lower risk of T2D. Spline analysis showed that a Cu-Zn ratio intake < 0.30 was associated with a lower risk of T2D and that there was no departure from a linear association ( P  = 0.1180). There was an interaction between the Cu-Zn ratio and BMI on T2D risk ( p Interaction  = 0.0010) but not smoking status ( p Interaction  = 0.6956). Cu-Zn ratio was positively associated with T2D only in obese women, but not in normal-weight or overweight women. Conclusions: Our findings suggest that a lower dietary Cu-Zn ratio intake is associated with a lower T2D risk, especially among obese women. Further studies are warranted to validate our results and determine whether the associations are similar in men. Funding Sources: This work was supported by a grant for the E4N study project by the Agence Nationale de Recherche and by a grant for the Nutriperso Project (IDEX Paris Saclay).